Notary's Responsibility for The Inheritance Deed Regarding Legal Risks for The Heirs - Wicakosono, Katon (Jurnal Konstatering, 2025)
This study discusses the notary's responsibility for inheritance certificates regarding legal risks for heirs. Inheritance issues are one of the issues that often cause disputes. Inheritance is closely related to property. Conflicts about inheritance generally revolve around two things: who is the heir and how much each heir's share is. A notary is a public official who is solely authorized to make authentic deeds. One of the deeds made by a notary is an Inheritance Certificate. The objectives of this study are to analyze: 1) The notary's responsibility for the inheritance certificate he/she makes. 2) The legal provisions in making inheritance certificates to avoid legal risks for heirs. This research method is normative juridical research with a statute approach. The type of research is normative. The data sources in this study are secondary data, consisting of primary legal materials, secondary legal materials, and tertiary legal materials. In this study, data collection was carried out through a literature study and then analyzed using legal prescriptive methods. The results of this study indicate that the notary's responsibility for the deed of inheritance statement he made has a big influence on the heirs, because if the making is not in accordance with the applicable provisions, it will cause disputes. In making a deed of inheritance statement, the notary must be careful in making the deed of inheritance because it can cause undesirable things and legal provisions in making a deed of inheritance statement to avoid legal risks for the heirs. In making a deed of inheritance statement, the community must pay attention to the legal provisions or conditions that must be met, so that the heirs avoid legal risks and the notary avoids legal risks, the notary before making a Certificate of Inheritance, the notary needs to carry out formalities such as viewing and examining documents related to the Inheritance and on the basis of these documents a Deed of Declaration of Heir is made.